Diversity of the fecal microbiota in Chinese ponies - Lv, Shipeng; Zhang, Yanli; Zhang, Zhengkai; Meng, Sihan; Pu, Yabin; Liu, Xuexue; Liu, Lingling; Ma, Yuehui; Liu, Wujun; Jiang, Lin (Frontiers in Veterinary Science, 2023)
Horse gut microbiomes are rich and complex that has important roles in horse growth and development. To date, information on microbial diversity in the gut of the ponies from different populations remains limited. In this article, 118 fecal samples from DeBa pony, NiQi pony and GuZh horse were studied by pyrosequencing the 16S V3–V4 hypervariable regions using the Illumina Miseq platform. Differences in gut microbiota composition between breeds were determined using diversity analysis. The alpha diversity analysis showed that NiQi ponies had a more abundant and diverse gut microbiota. Subsequent cluster analysis showed that DeBa pony have a microbiota composition more similar to NiQi pony. LEfSe analysis revealed that the bacterial biomarkers for NiQi pony at the genus level were Phascolarctobacterium, Paludibacter, and Fibrobacter; the bacterial biomarker for DeBa pony was Streptococcus and Prevotella; and the bacterial biomarkers for GuZh horses was Treponema, Treponema Mogibacterium, Adlercreutzia and Blautia. The correlation analysis between genera with >1% abundance and horse height found that Streptococcus (P<0.01), Treponema(P<0.01), Coprococcus(P<0.01), Prevotella (P<0.01), Phascolarctobacterium(P<0.01), and Mogibacterium(P<0.01) were significantly associated with horses’ height. The functional prediction results indicated that DeBa pony have a microbiota functional more similar to NiQi pony. For the first time, our results reveal the species composition and structure of the gut microbiota of ponies in China. These microbial community profiles can be used as references for future research on the microbiome associated with health and development in the ponies population.